Research problems in prof. J. Matulionis competition of young mathematicians - Narkevičienė, Bronė; Papreckienė, Laima; Dabrišienė, Vilija (Lietuvos matematikos rinkinys, 2002)
This article presents analysis results of research problems in prof. J. Matulionis competition of young mathematicians.